2021
DOI: 10.1186/s13002-021-00457-w
|View full text |Cite
|
Sign up to set email alerts
|

Contested or complementary healing paradigms? Women’s narratives of COVID-19 remedies in Mwanza, Tanzania

Abstract: Background COVID-19 has caused worldwide fear and uncertainty. Historically, the biomedical disease paradigm established its dominance in tackling emerging infectious illnesses mainly due to innovation in medication and advances in technology. Traditional and religious remedies have emerged as plausible options for prevention and treatment of COVID-19, especially in Africa and Asia. The appeal of religious and traditional therapies against COVID-19 in the African setting must be understood with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Health care for children under five is free at public facilities but the quality of the services is often inadequate, and many people, including the poor, opt for private health services. In addition to professional health providers, Tanzanians make use of a wide range of healing paradigms [38][39][40].…”
Section: Setting Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Health care for children under five is free at public facilities but the quality of the services is often inadequate, and many people, including the poor, opt for private health services. In addition to professional health providers, Tanzanians make use of a wide range of healing paradigms [38][39][40].…”
Section: Setting Of the Studymentioning
confidence: 99%
“…A central finding of this study is that caregivers rely on their personal experiences, or advice from family and friends when choosing to take a child for uvulectomy. Medical anthropologists have pointed out that experiences "are generated relationally" [52] and other studies from Tanzania have shown that social relations are central for treatment-seeking practices, and that trust in certain forms of treatment is "reinforced through social recommendation" [40]. There is therefore a possibility that the acceptability of uvulectomy can increase in the urban context, rather than decrease.…”
Section: The Perceived Efficacy Of Uvulectomy and Few Negative Outcomesmentioning
confidence: 99%
“…Some preventative remedies include steam inhalation, drinking herbal juices, decoction (Kadha) and hot water; these are mainly used in Asian countries like Bangladesh, Pakistan, and India 24,29,45 . Vitamin C and concoctions containing garlic, lemon and ginger, other native herbs and warm water are commonly used in Africa 30–32 . Despite having no pharmacological rationale for using these remedies, they have proven effective.…”
Section: Resultsmentioning
confidence: 99%
“…24,29,45 Vitamin C and concoctions containing garlic, lemon and ginger, other native herbs and warm water are commonly used in Africa. [30][31][32] Despite having no pharmacological rationale for using these remedies, they have proven effective.…”
Section: Theme 1: Remedies For the Treatment Of Covid-19mentioning
confidence: 99%
“…15,16 Ocimum species have historically been used to control the COVID-19 epidemic, particularly in developing nations. 17,18 Ocimum americanum, commonly known as hoary basil, and Ocimum basilicum, also known as sweet basil leaves, are 2 plant species that belong to the Ocimum species and are utilized extensively for their many medicinal uses. Numerous chemicals found in these plants, including tannins, carotenoids, flavonoids, and estragole, have anti-inflammatory, antioxidant, antiviral, hypoglycemic, hypolipidemic, antibacterial, anticancer, and wound-healing properties.…”
Section: Introductionmentioning
confidence: 99%